2013
DOI: 10.1038/ncomms3340
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale dynamic process of deformation-induced stacking fault tetrahedra in gold nanocrystals

Abstract: Stacking fault tetrahedra, the three-dimensional crystalline defects bounded by stacking faults and stair-rod dislocations, are often observed in quenched or irradiated face-centred cubic metals and alloys. All of the stacking fault tetrahedra experimentally observed to date are believed to originate from vacancies. Here we report, in contrast to the classical vacancyoriginated ones, a new kind of stacking fault tetrahedra formed via the interaction and crossslip of partial dislocations in gold nanocrystals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(24 citation statements)
references
References 48 publications
3
20
1
Order By: Relevance
“…Importantly, it was explicitly concluded that vacancies were not involved, and for many years this has been the accepted view for tetrahedra formed in deformed metals. This conclusion is contrary to many statements made in the paper by Wang et al [5]. For example, among other assertions they state:…”
contrasting
confidence: 81%
See 2 more Smart Citations
“…Importantly, it was explicitly concluded that vacancies were not involved, and for many years this has been the accepted view for tetrahedra formed in deformed metals. This conclusion is contrary to many statements made in the paper by Wang et al [5]. For example, among other assertions they state:…”
contrasting
confidence: 81%
“…Figure 2, which is Figure 2(g) from Wang et al's paper [5], is reproduced below, where the stacking faults on b, c and d were observed to be formed by partial dislocations gliding in from the surface of the nanocrystal.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These defects can occur more frequently in crystalline films that are grown on substrates with different lattice. SFs are typically considered to be undesired defects that lower the film structural properties and therefore much effort is done to avoid their formation12. However, they also show intriguing electronic properties34 that may be exploited if they can be created in a controlled manner.…”
mentioning
confidence: 99%
“…Figure 3(a) presents a formation progression of normal bcc structure-SF-twin, in terms of stacking sequences along the close-packed direction [111]: a SF involves only one faulted plane of stacking, 62 while twins involve two or more faulted planes, where the crystal lattice symmetry is broken and the lattice becomes a mirror image of itself. 63 (Stable SFs are observed to nucleate from the GB with h ¼ 0 ; however, twins are observed in grain interiors for all grain orientations, as well as all GBs except for h ¼ 0…”
Section: A Deformation Of the Nanopillar With H50 And Mechanismsmentioning
confidence: 99%